2015
DOI: 10.1007/s10903-015-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

A Path Analysis of Mental Health Among Thai Immigrant Employees in Pranakron Si Ayutthaya Province

Abstract: The aims of this research were to study both direct and indirect path analyses of mental health, and to analyse a causal relationship of each variable. A cross-sectional study used stratified random sampling to select Thai immigrant employees in Pranakron Si Ayutthaya Province, Thailand. General data were analysed by number and percentage. The mental health variable was measured by THMHI-15. The latter was analysed by general statistic, and a path analysis. The results found that job conditions and distance tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The results founded by Kaewanuchit highlight that job conditions and distance travelled between house and workplace had a direct effect on mental health with a standardized regression weight of 0.581 and 0.443, respectively (p < 0.01). It was found that housing conditions had no effect on mental health, conversely the income variable had a direct influence on mental health with a standardized regression weight of 0.68 (p = 0.01) [119].…”
Section: Poor Mental Healthmentioning
confidence: 95%
“…The results founded by Kaewanuchit highlight that job conditions and distance travelled between house and workplace had a direct effect on mental health with a standardized regression weight of 0.581 and 0.443, respectively (p < 0.01). It was found that housing conditions had no effect on mental health, conversely the income variable had a direct influence on mental health with a standardized regression weight of 0.68 (p = 0.01) [119].…”
Section: Poor Mental Healthmentioning
confidence: 95%
“…When Thai society formed the AEC (Asian Economic Community) society two years ago, a researcher in Thailand studied the path analysis of mental health among Thai immigrant employees who worked in Pranakron Si Ayutthaya Province, Thailand. It found that job conditions and the distance travelled between their home and workplace had a direct effect on mental health [1]. This research implied that job conditions were an important factor related to mental health [1].…”
Section: Introductionmentioning
confidence: 75%
“…It found that job conditions and the distance travelled between their home and workplace had a direct effect on mental health [1]. This research implied that job conditions were an important factor related to mental health [1]. This point reflected that not only national migration but also international migration is sensitive, especially, among Asian immigrant employees (e.g.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These are also found among females who were working as maids [24]. That is to say, job conditions were important factor that contributed to mental health [17]. It is important and necessary to compare the causal relationships and job stress among employees between those who were supporting their aging parents to the other group who were not.…”
Section: Introductionmentioning
confidence: 99%